Genetic characterization of four generations of Oreochromis niloticus subjected to individual selection in southern Brazil - Silva, Bruno Corrêa; Pereira, Adriana; Massago, Haluko; Mariguele, Keny Henrique (Revista de Ciências Agroveterinárias, 2025)
The process of artificial selection can lead to a rapid decrease in genetic variability across generations, consequently reducing the response to selection in a breeding program. Therefore, understanding the genetic characteristics of the breeding stock is essential, making it important to assess inbreeding and allele frequency changes over generations. In this context, the present study performed the genotypic characterization of four generations of Nile tilapia subjected to individual selection for final weight, aiming to evaluate inbreeding and changes in allele frequencies across generations. The first four generations of GIFT tilapia from the Epagri breeding program were characterized using 11 microsatellite markers. There was only a 5.2% reduction in the total number of alleles across generations. The average number of effective alleles per marker remained similar across generations (4.07 ± 0.4 for G1; 3.88 for G2; 3.86 for G3; and 3.87 for G4). Overall, observed heterozygosity was higher than expected heterozygosity, leading to FIS values of -0.042, 0.027, -0.042, and -0.017 for G1, G2, G3, and G4, respectively. Therefore, individual selection did not result in significant losses of genetic variability across generations; however, significant changes in allele frequencies were observed at some loci, which genetically differentiated the generations from one another. Genotypes clustered by the Bayesian method identified 9 groups in G1, 16 groups in G2, and 12 groups in both G3 and G4. Thus, using the microsatellite markers, it was possible to genetically characterize the breeding stocks of four generations of the Epagri tilapia breeding program, and an adequate maintenance of genetic variability in the stock was observed, allowing for the program's continuity. However, important changes in allele frequencies were also detected in the evaluated markers as a result of the applied selection.